Simeprevir, daclatasvir and sofosbuvir for hepatitis C virus‐infected patients with decompensated liver disease. Issue 4 (23rd November 2016) - Lawitz, E.; Poordad, F.; Gutierrez, J. A.; Kakuda, T. N.; Picchio, G.; Beets, G.; Vandevoorde, A.; Van Remoortere, P.; Jacquemyn, B.; Luo, D.; Ouwerkerk‐Mahadevan, S.; Vijgen, L.; et al.
Summary: Approximately three million individuals in the United States are chronically infected with hepatitis C virus (HCV). Chronic HCV infection may lead to the development of compensated as well as decompensated liver cirrhosis. The Phase II IMPACT study was conducted in HCV genotype 1‐ or 4‐infected cirrhotic patients with portal hypertension or decompensated liver disease and assessed for the first time the combination of the three direct‐acting antivirals simeprevir, daclatasvir and sofosbuvir. Treatment‐naïve or treatment‐experienced adults with Child‐Pugh (CP) score <7 (CP A) and evidence of portal hypertension, or CP score 7–9 (CP B), received 12 weeks of simeprevir 150 mg, daclatasvir 60 mg and sofosbuvir 400 mg, once daily. The primary efficacy endpoint was sustained virologic response 12 weeks after end of treatment (SVR12). Pharmacokinetics and safety were also assessed. Overall, 40 patients were enrolled (CP A: 19; CP B: 21). All 40 patients achieved SVR12. At week 8, the mean pharmacokinetic exposure to simeprevir, sofosbuvir, daclatasvir and GS‐331007 (sofosbuvir metabolite) was 2.2‐, 1.5‐, 1.2‐ and 1.2‐fold higher in patients with CP B than CP A, respectively. Grade 1/2 adverse events (AEs) occurred in 26 of 40 (65%) patients. One CP B patient had a Grade 3 AE (gastrointestinal haemorrhage), which was reported as a serious AE but not considered related to study drugs. Treatment for 12 weeks with simeprevir, daclatasvir and sofosbuvir was generally safe and well tolerated, and resulted in 100% of cirrhotic patients with portal hypertension or decompensated liver disease achieving SVR12.